Peregrine Financial Group : misappropriating customer funds - Oji, Chijioke (SAGE knowledge. Cases., 2016)
In early July 2012, the United States Commodity Futures Trading Commission (CFTC) filed a federal lawsuit against Peregrine Financial Group Inc. (PFG), a futures trading firm, and its founder Russell Wasendorf. The CFTC accused PFG and Wasendorf of fraud, violating customer funds amounting to US$215 million and submitting false financial reports to the National Futures Association (NFA), which operated under the CFTC's supervision. PFG faced liquidation and Wasendorf, if found guilty, faced a fine or a jail sentence.